Subalpine vegetation changes in the Eastern Sudetes (1973–2021): Effects of abandonment, conservation management and avalanches - Klinkovská, Klára; Kučerová, Anna; Pustková, Štěpánka; Rohel, Jaroslav; Slachová, Karolína; Sobotka, Vojtěch; Szokala, Daniel; Danihelka, Jiří; Kočí, Martin; Šmerdová, Eva; Chytrý, Milan (Applied vegetation science, 2023)
Aims The summit grasslands of many European mountain ranges were historically used for summer grazing, which ceased in the 20th century. These grasslands are changing, partly through succession after abandonment and partly owing to environmental changes. Subalpine vegetation is also affected by artificially reduced avalanche frequency. Recent conservation efforts have attempted to reverse the negative trends of change. We ask: (1) How has subalpine vegetation changed following the abandonment and avalanche control? (2) Was conservation management able to reverse the post‐abandonment trend of vegetation change? (3) Did avalanche disturbance have a positive effect on plant species diversity? Location Summit area of the Hrubý Jeseník Mountains (1,491 m a.s.l.), Eastern Sudetes, Czech Republic. Methods Vegetation plots sampled in the 1970s were resurveyed in the 2000s and again in 2021. Subalpine vegetation was classified into six types, and transitions between these types over time were quantified. Vascular plant species richness and the proportion of threatened species were compared between periods, between areas with and without conservation management, and between areas affected vs unaffected by a large avalanche from 2019. Species composition was analysed using principal coordinate analysis and distance‐based redundancy analysis. Results Vegetation types remained relatively stable except for species‐rich grasslands, some of which changed to heathlands or tall‐forb vegetation. Some competitive species have increased, and species specialized to threatened habitats declined. Conservation management systematically implemented after 2010 slowed the decline of habitat‐specialized species but did not reverse it. Disturbance by an avalanche positively affected species richness but not the number of threatened species. Conclusions Subalpine vegetation is slowly losing its plant diversity owing to grazing cessation and possibly acidification from past atmospheric deposition. Recently implemented conservation management and restoration of avalanche activity are essential to stop this trend, but future monitoring is needed to evaluate the success of management actions. Subalpine plant communities in the Hrubý Jeseník Mountains (Czech Republic) were repeatedly sampled in the 1970s, 2000s and 2021. Although vegetation changes were not large, species‐rich grasslands lost some of their habitat‐specialized species. Conservation management partly slowed this process but did not reverse it. Disturbance by an avalanche positively affected species richness but not the number of threatened species.